Blood Impairs Viability of Fat Grafts and Adipose Stem Cells: Importance of Washing in Fat Processing. (20th June 2020) - Jin, Shengyang; Yang, Zhibin; Han, Xuefeng; Li, Facheng
Abstract: Background: Fat processing plays a pivotal role in graft survival. Each component of the blood in lipoaspirate affects fat survival in different ways, but the mechanisms are not clear. Objectives: The aim of this study was to investigate, by various experimental methods, the effect of blood on the viability of fat grafts and adipose stem cells (ASCs). Methods: Blood and fat samples were obtained from 6 female patients undergoing aesthetic liposuction. For the in vivo experiment, we compared fat mixed with normal saline or various ratios of blood in nude mice. The samples were explanted at 2 and 8 weeks to evaluate the gross volume retention and histologic and immunohistochemical characteristics. For in vitro experiments, ASCs were pretreated with hemoglobin at different concentrations and for different times. We then assessed the proliferation, migration, adipogenesis, and reactive oxygen species production of ASCs. Results: Blood in the graft led to a decrease in graft viability, as evaluated by general observation and histologic and immunohistochemical morphology in vivo. In vitro experiments showed inhibited proliferation, migration, and adipogenesis, and increased reactive oxygen species production in ACSs, after hemoglobin treatment, suggesting impaired ASC viability. Conclusions: This study suggests that blood impairs the viability of fat grafts and ASCs and provides evidence that washing to remove blood is important in fat processing.